Methanogenesis control in bioelectrochemical systems: A carbon footprint reduction assessment. Issue 1 (February 2018) - Jobin, Lucas; Jose, Catherine; Pages, Christophe; Raffin, Guy; Saupin, Xavier; Jame, Patrick; Jaffrezic-Renault, Nicole; Namour, Philippe
Graphical abstract: Highlights: Decrease in carbon footprint (CF) by 22% with anodic methanogenic biofilms poised at +300 mV. 1, 5 times less CH4 but 10 times more CO2 in closed- circuit than open-circuit. 3 times more greenhouse gases in closed circuit than in open-circuit. False value of CF when pressure is not taken into account (+22% error). False value of CF when pressure and CO2 are not taken into account (+68% error). Abstract: Are bioelectrochemical systems suitable to fight against the global warming provoked by the anthropogenic sources of CH4 ? None of the existing studies on this topic provide clear answers because the performance criteria of the electrochemical treatment and gas quantification methods used so far are questionable. This article redefines this performance criteria (carbon footprint – CF) and shows the importance of the materials and methods used to assess this criteria. Indeed, inappropriate gas quantification methods (pressure not taken into account, quantification only of CH4 and not of CO2 ) lead to errors on calculating the CF reduction rate from 22% to 68% in closed system. Moreover, this article demonstrates, based on suitable gas quantification methods and by means of triplicate MECs with the anode potential poised at +300 mV with respect to the Ag/AgCl reference, that it is possible to achieve a significant reduction in the CF of 22% of anaerobic biofilms producing CO2 and CH4 .